The KdpD/KdpE two-component system contributes to the motility and virulence of avian pathogenic Escherichia coli. (August 2020) - Xue, Mei; Raheem, Muhammad Akmal; Gu, Yi; Lu, Huiqi; Song, Xiangjun; Tu, Jian; Xue, Ting; Qi, Kezong
Abstract: Two-component systems (TCSs) are widespread regulatory systems which can help bacteria to control their cellular functions and respond to a diverse range of stimuli. The KdpD/KdpE system had been well studied for regulating potassium transport and identified as an adaptive regulator involved in the virulence of some pathogenic bacteria, but its role in avian pathogenic Escherichia coli (APEC) was still unknown. In this study, the mutant strain AE17Δ KdpDE was obtained successfully of a clinical APEC isolation AE17 using the lambda Red recombinase system and performed the transcriptional sequencing of the wild type strain AE17 and the mutant strain AE17Δ KdpDE . The transcriptional sequencing results revealed that the KdpD/KdpE two-component system mainly influenced the expression of the genes covering metabolic pathways, flagellar assembly, global transcription regulator. The expression of some flagellar-related genes detecting by quantitative real-time PCR was consistent with the results of transcriptional sequencing. Importantly, fewer flagellum of the mutant strain AE17Δ KdpDE was observed than AE17 using the transmission electron microscope and a decreased motility circle of AE17Δ KdpDE appeared in the semisolid medium. In addition, the serum bactericidal assay was carried out with the specific-pathogen-free chicken in different dilution and the survival ability in the serum of AE17Δ KdpDE was also obviously lower than that of AE17. These results suggested that in APEC, the KdpD/KdpE two-component system mainly influenced the expression of flagella-related genes, the flagellum formation, the motility and antiserum bactericidal activity. Graphical abstract: Unlabelled Image Highlights: The first work to study the function of the KdpD/KdpE two-component system in avian pathogenic Escherichia coli . The first study showing the KdpD/KdpE two-component system contributed to the expression of some flagella-related genes, flagella formation and motility in avian pathogenic Escherichia coli . The first study showing the KdpD/KdpE two-component system influenced the antiserum bactericidal activity of avian pathogenic Escherichia coli .